Pipelined processor farms : structured design for embedded parallel systems - Fleury, Martin, 1951-; Downton, A. C. (New York : Wiley, 2001)
This book outlines a methodology for the use of parallel processing in real time systems. It provides an introduction to parallel processing in general, and to embedded systems in particular. Among the embedded systems are processors in such applications as automobiles, various machinery, IPGAs (field programmable gate arrays), multimedia embedded systems such as those used in the computer game industry, and more.
Basic Concepts -- PPF in Practice -- Development of PPF Applications -- Initial Development of an Application -- Graphical Simulation and Performance Analysis of PPFs -- Template-based Implementation -- Application Examples -- Design Studies -- Counter Examples -- Performance of PPFs -- Instrumentation of Templates -- Future Trends.
Includes bibliographical references (pages 269-298) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
John Wiley and Sons
Keywords: Embedded computer systems -- Programming; Parallel computers -- Programming; x; x; REFERENCE -- General; Embedded computer systems -- Programming; Parallel computers -- Programming; Eingebettetes System; Parallelrechner; Pipeline-Verarbeitung